ANALISIS KINERJA SIMPANG EMPAT TERHADAP TINGKAT PELAYANAN DENGAN MENGGUNAKAN SOFTWARE PTV VISSIM - Yunita, Nurma; Windari, Aulia Choiri; Sari, Ribut Nawang (Teknik Sipil, Politeknik Negeri Ketapangg, 2024)
Simpang Empat Duren Tiga in South Jakarta, involving Jl. Duren Bangka, Jl. Duren Tiga, Jl. Mampang Prapatan Raya, and Jl. Hj. Tutty Alawiyah, often experiencing congestion due to dense traffic flow and disruption on roads during peak hours. This study analyzed the capacity, queue length, and delays to reduce congestion. The Data used include primary data from field surveys and observations, as well as secondary data on the number of city residents. The purpose of this analysis is expected to improve the performance of intersections that often experience traffic conflicts. This analysis uses the PTV vissim Software method, there are 2 alternative improvements used in the study, namely Alternative 1-rearrangement of traffic light signals and changes in signal phase, alternative 2 – making changes to road widening. The results obtained from this study in the southern approach sebeum existence of alternative solutions obtained an average queue length of 69.183 m, the average delay of vehicles 69.643 seconds/vehicle, and the average delay of all road users 69.643 seconds / vehicle, so that the level of service performance obtained intersection F. After alternative solutions, the results obtained on the southern approach with an average queue length of 64.849 m, the average delay of vehicles 20.437 seconds/vehicle, and the average delay of all road users 17.254 seconds/vehicle, so that the level of service performance of the intersection increased to C. Keywords: junction performance, queue length, PTV vissim, delay